Drinking Power: Alcohol and History in Africa - Willis, Justin (History compass, 2005)
This article surveys the literature on alcohol in Africa. It suggests that the trajectory of this literature has very much followed that of African history generally: beginning with a focus on the colonialism itself; then moving to an exploration of African ‘resistance’; and then into studies of the post-colonial state and approaches which have emphasized the importance of cultural continuity, and African agency. While history writing has tended to see alcohol essentially as a way of exploring larger processes of social change, there has been a largely unstated rift in the wider literature on alcohol in Africa between, on the one hand those who view alcoholic beverages - and especially novel beverages - as drivers of change in themselves; and on the other hand those who see the potency of alcohol as essentially ascribed, and view the study of drink principally as a window on other processes of change.